Umpan Balik 360 Derajat pada Organisasi Pendidikan: Tinjauan Sistematis dalam Penilaian Kinerja - Ishmah Rafidatuddini; Umi Anugerah Izzati (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
Effective performance evaluation is a critical element in improving the quality of education. One increasingly recognized evaluative approach is 360-degree feedback, which integrates input from multiple sources such as supervisors, colleagues, subordinates, students, and self-assessment. This study aims to explore the implementation, benefits, and challenges of 360-degree feedback in educational organizations through a literature review method. Literature was gathered from academic databases such as Google Scholar, Scopus, and ScienceDirect using relevant keywords and a publication range from 2020 to 2024. Out of 200 initially identified articles, nine were selected based on established inclusion and exclusion criteria. The review findings indicate that 360-degree feedback enhances objectivity in evaluation, promotes professional development, and strengthens a culture of reflection and collaboration within educational institutions. However, its effectiveness depends on organizational readiness, the quality of the evaluation instruments, and environmental support. These findings affirm that 360-degree feedback is a strategic tool for more comprehensive and improvement-oriented performance evaluation in the education sector